2008
DOI: 10.1007/s10964-008-9332-5
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress as a Mediator of the Relationship Between Trauma and Mental Health Problems Among Juvenile Delinquents

Abstract: This study investigated the interrelationships among trauma exposure, PTSD, and mental health problems in a sample of 289 adolescents (199 male, 90 female) detained in a juvenile correctional facility. Mean differences were found in that females scored higher than males on measures of interpersonal trauma exposure and symptoms of both simple and complex PTSD. Females also endorsed more mental health problems in the areas of depression/anxiety, somatic complaints, and suicidal ideation. For all youth, trauma ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
135
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 49 publications
20
135
0
2
Order By: Relevance
“…Longitudinal research has identified adolescence as a developmental period in which individuals are particularly susceptible to experiencing trauma and, in turn, developing PTSD 7 . Many studies confirm that PTS symptoms are quite prevalent among youth and are associated with health problems 9,10,23 . Our study supported this idea, as the associations between all the investigated health complaints and PTS symptoms were significant (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research has identified adolescence as a developmental period in which individuals are particularly susceptible to experiencing trauma and, in turn, developing PTSD 7 . Many studies confirm that PTS symptoms are quite prevalent among youth and are associated with health problems 9,10,23 . Our study supported this idea, as the associations between all the investigated health complaints and PTS symptoms were significant (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, findings indicate that there may be gender differences in the types of trauma experienced by youth. For example, girls are more likely than boys to report that they were the direct victims of trauma, whereas boys were more likely to report witnessing violence [6,31]. Additionally, girls are more likely to experience trauma involving sexual abuse or rape than boys [24].…”
Section: Predictors Of Female Persistencementioning
confidence: 99%
“…During the in-depth interviews, the researcher found that they had traits of post-traumatic stress disorders [20].…”
Section: Exposure To Traumatic Eventmentioning
confidence: 99%